Perancangan Sistem Informasi Pelaporan Klaim BPJS Rawat Jalan Tidak Layak Menggunakan Metode V-Model - Karmila, Ira; Syahidin, Yuda; Gunawan, Erix (Program Studi Teknik Informatika Universitas Pamulang, 2024)
The purpose of this research is to design an ineligible outpatien BPJS claim reporting information system implemented in Microsoft Visual Studio 2012. A qualitative methodology based on descriptive statistics was employed for the investigation. Observation and interviews with hospital claims officials were the methods utilized to gather data. We utilize the v-model, a variant of the waterfall approach, to build our software. The investigation revealed certain issues, such as the persistence of infeasible BPJS outpatient claims and the persistence of traditional reporting methods. Reports detailing the total number of BPJS claims that were deemed ineligible are generated by the intended information system. It is believed that health institutions will be able to use this design's findings to streamline the process of following up on accusations that BPJS has returned to hospitals.